Menanti Kesiapan Daerah Menerima Kesempatan Dan Tantangan Penerbitan Obligasi Daerah Sebagai Alternatif Pembiayaan - Fitria, Rizky (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2010)
The end of the balanced budget principle gave opportunities to local governments in Indonesia to issue bonds as a financing alternative. The issuance of bonds to provide many benefits to the region, especially in financing projects quite fundamental. the bonds also cause a variety of risks and obligations to local government as issuer (the issuer). The risk is entirely borne by local governments and not helped by the central government. Therefore, the issuance of municipal bonds must go through a fairly complicated series of stages. Local government discreetness is required here. Kinds of benefits and risks that arising in connection with the issuance of municipal bonds is the opportunity and challenge for local governments. From the beginning of this opportunity thrown, no local government dare to answer the challenge by issuing municipal bonds. This raises a question mark, when local governments are willing to answer the challenge and take advantage of it.